Introduction to Hegel’s Introduction to philosophy - Giusti, Miguel (Estudios de Filosofía, 1992)
The article sets forth a series of hermeneutical considerations regarding philosophers and their writings; it then centers on the problems Hegel finds in the philosophy of his age: the crisis of the Enlightment, of Kantian morality, and interest in ancient Greece. It finally makes an exposition of Hegel’s conception of Phenomenology of Spirit as an introduction to philosophy, understood by him as Science.